2021
DOI: 10.1007/s10531-021-02212-9
|View full text |Cite
|
Sign up to set email alerts
|

Landscape features associated to wind farms increase mammalian predator abundance and ground-nest predation

Abstract: Wind farm implementation is a rapidly growing source of landscape transformation that may alter ecological processes such as predator-prey interactions. We tested the hypothesis that wind farms increase the activity of nest predators and, ultimately, increment ground-nest predation rates. We placed 18 plots in Iberian shrub-steppes (11 at control and seven at wind farm sites), each one comprised nine artificial ground-nests (three quail eggs/nest). Artificial nests were placed during two events: at the beginni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 90 publications
1
11
0
Order By: Relevance
“…Moreover, we also found that the variance explained by our model was higher when considering the random variable year, which could be due to the potential influence of yearly weather variablility and related food supply on the H/L ratio values (Norte et al 2009a;Banbura et al 2013;Fairhurst et al 2013). Finally, we cannot exclude the role of the high nest predation rates reported in this species (over 80% of nests in some Spanish populations, Herranz et al 1994;Pérez-Granados et al 2017;Gómez-Catasús et al 2021) and other berian groundnesting shrubsteppe passerines (> 70%, Suarez et al 1993, Yanes andSuárez 1995) in explaining the observed H/L ratio seasonal differences.…”
Section: Spatio-temporal Variationmentioning
confidence: 71%
“…Moreover, we also found that the variance explained by our model was higher when considering the random variable year, which could be due to the potential influence of yearly weather variablility and related food supply on the H/L ratio values (Norte et al 2009a;Banbura et al 2013;Fairhurst et al 2013). Finally, we cannot exclude the role of the high nest predation rates reported in this species (over 80% of nests in some Spanish populations, Herranz et al 1994;Pérez-Granados et al 2017;Gómez-Catasús et al 2021) and other berian groundnesting shrubsteppe passerines (> 70%, Suarez et al 1993, Yanes andSuárez 1995) in explaining the observed H/L ratio seasonal differences.…”
Section: Spatio-temporal Variationmentioning
confidence: 71%
“…Clutch size usually varies between three and six eggs, with an incubation period of 11-14 days. fledglings leave the nest at between eight days (Dupont's lark) and 14 days (Tawny Pipit) (Calero-riestra & García, 2019;Cramp & Simmons, 1980;Gómez-Catasús et al, 2016;herranz et al, 2004;Pérez-Granados et al, 2016;Suárez, 1977).…”
Section: Study Speciesmentioning
confidence: 99%
“…The only exception is Dupont's lark, the resident species, whose first detected nesting attempt was in mid-March, coinciding with the start of the nest surveys. however, it is known that its reproductive period can extend from mid-late february to early July (Gómez-Catasús et al, 2016), though early dates may correspond with warmer locations in South or North-East Spain. In general, the dates provided in this work with those described so far for the Eurasian Skylark and the Western Black-eared Wheatear (Collar, 2021;.…”
Section: Reproductive Phenology and Nest Structurementioning
confidence: 99%
“…As an initial illustration of the method's practical relevance, we here present an incomplete list of recent applications. In the time-period of May-Sep 2021, we find applications of the SPDE-approach to Gaussian fields in astronomy (Levis et al, 2021), health (Mannseth et al, 2021;Scott, 2021;Moses et al, 2021;Bertozzi-Villa et al, 2021;Moraga et al, 2021;Asri and Benamirouche, 2021), engineering (Zhang et al, 2021), theory (Ghattas and Willcox, 2021;Sanz-Alonso and Yang, 2021a;Lang and Pereira, 2021;Bolin and Wallin, 2021), environmetrics Beloconi et al, 2021;Vandeskog et al, 2021a;Wang and Zuo, 2021;Wright et al, 2021;Gómez-Catasús et al, 2021;Valente and Laurini, 2021b;Bleuel et al, 2021;Florêncio et al, 2021;Valente and Laurini, 2021a;Hough et al, 2021), econometrics (Morales and Laurini, 2021;Maynou et al, 2021), agronomy (Borges da Silva et al, 2021), ecology (Martino et al, 2021;Sicacha-Parada et al, 2021;Williamson et al;Bell et al, 2021;Humphreys et al;Xi et al, 2021;Fecchio et al), urban planning (Li, 2021), imaging (Aquino et al, 2021), modelling of forest fires (Taylor et al; Lindenmayer et al), fisheries (Babyn et al, 2021;van Woesik and Cacciapaglia, 2021;Jarvis et al, 2021;…”
Section: Some Recent Applicationsmentioning
confidence: 99%